New Aquilariomyces and Mangifericomes species (Pleosporales, Ascomycota) from Aquilaria spp. in China - Tian-Ye Du; Samantha C. Karunarathna; Kevin D. Hyde; Somrudee Nilthong; Ausana Mapook; Dong-Qin Dai; Kunhiraman C. Rajeshkumar; Abdallah M. Elgorban; Li-Su Han; Hao-Han Wang; Saowaluck Tibpromma (MycoKeys)
Saprobic fungi are known for their critical role in decomposition and nutrient cycling. The study of saprobic fungi is equally important, as it helps in understanding their ecological roles and identifying their hidden diversity. This study focused on saprobic fungi on Aquilaria, which is poorly studied compared to economically important hosts like coffee, tea, and rubber. Our rigorous process led to the collection of two new terrestrial saprobic fungi from the Guangdong and Yunnan provinces in China. After extensive phylogenetic analyses and detailed comparison of morphological characteristics, the two collections were identified as two new species belonging to Pleosporales, Ascomycota. Aquilariomyces maomingensis sp. nov. was isolated from Aquilaria sinensis in Guangdong Province, while Mangifericomes aquilariae sp. nov. was isolated from Aquilaria sp. in Yunnan Province. Full descriptions, photo plates, and phylogenetic analyses (maximum likelihood and Bayesian inference analyses based on LSU, ITS, SSU, tef1-α, and rpb2 gene combinations) of the new species are provided, along with a comprehensive list of saprobic fungi associated with Aquilaria spp.